Structured Assessment of Violence Risk in Youth in clinical practice - Kostic, Jelena Slavko; Stojanović, Aleksandra; Stanković, Miodrag; Žikić, Olivera (Acta medicae Medianae, 2021)
Introduction Violence risk assessment in adolescents is an emergent research area with great potential for clinical application. The need for standardization of clinical approaches has led to the development of structured professional judgment tools for violence risk assessment in youth. The aim of the study was to present a structured evaluation of violence risk assessment in clinical work with two male patients, ages 12 and 17 with a psychiatric diagnosis of Conduct disorder, socialized type, i.e. Acute psychotic disorder. The Structured Assessment of Violence Risk in Youth TM (SAVRY) was used in the assessment to help estimate the patients’ risk for future violence. Discussion Based on the systematic analysis and consideration of the SAVRY Historical, Socio-Contextual and Individual risk factors balanced against the Protective factors, both patients were rated as being at High risk for future violence. In order to control and reduce the risk of further violent behaviour, an intervention plan was designed. Conclusion With the increasing recognition of the public health importance of violence, the violence risk assessment is the subject of considerable clinical and research interest. In this way, we are joining the global trend of opposing the social pathological emergence of violence among youth and violence in general.